2007
DOI: 10.1002/chem.200700126
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Induced Alterations in the Surface Population of Metal Sites in Bimetallic Nanoparticles

Abstract: The ability to alter the surface population of metal sites in bimetallic nanoparticles (NPs) is of great interest in the context of heterogeneous catalysis. Here, we report findings of surface alterations of Pt and Ru metallic sites in bimetallic carbon-supported (PtRu/C) NPs that were induced by employing a controlled thermal-treatment strategy. The thermal-treatment procedure was designed in such a way that the particle size of the initial NPs was not altered and only the surface population of Pt and Ru was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Proper annealing enables the modification of the imperfect Pt skin, which may improve the catalytic activity and stability. [22,40] These findings demonstrate the importance of appropriate treatment and could apply to other Pt bimetallic alloys associated with transition metals.…”
Section: Resultsmentioning
confidence: 93%
“…Proper annealing enables the modification of the imperfect Pt skin, which may improve the catalytic activity and stability. [22,40] These findings demonstrate the importance of appropriate treatment and could apply to other Pt bimetallic alloys associated with transition metals.…”
Section: Resultsmentioning
confidence: 93%
“…Li et al [23] and Takasu et al [24] also reported that heat treatment can increase specific activity of the PtRu catalyst. This behavior can be explained by Pt rich surface formation during the heat treatments under reducing atmosphere due to Pt-H interactions [25][26][27]. Figure 4 shows the CV results of the PtRu/C catalysts measured for 30 cycles.…”
Section: Resultsmentioning
confidence: 91%
“…66%) may assist the CO oxidation through a bifunctional mechanism [53]. Herein, we can summarize that the H570 has high I f /I b value, high EASA, and low onset potential for anodic CO stripping is probably assigned to the metallic Pt and Ru or PtO x species on the surface [42,58]. Nevertheless, the H570 cannot exhibit a comparative catalytic activity toward methanol decomposition at I 07 , suggesting that the surface amount of active sites for MOR is not sufficient.…”
Section: Resultsmentioning
confidence: 93%
“…5 shows the CO stripping scans recorded on the glassy carbon electrode of various PtRu/C catalysts in 0.1 M HClO 4 . It is generally accepted the fact that the activity for electrochemically [58]. For the O570 sample, the dramatically decreased EASA is observed due to a large amount of RuO 2 species occupied on the surface and a decrease in the number of Pt active sites accordingly.…”
Section: Resultsmentioning
confidence: 96%